Constructal view of the global circulation of the atmosphere, and flow architectures of river basins and lung tree”, Along with Constructal Theory, - Reis, A. Heitor (2012)
Review of recent developments on the flow structures: Global cirdulation of the atmosphere, River basins and lung tree.